Impact of top executive turnover on firms' R&D investment: evidence from China. Issue 3 (3rd July 2021) - Xiong, Ran; Wei, Ping; Yang, Jingyi; Cristofini, Luis Antonio
ABSTRACT: Though top executive turnover's economic consequence is highlighted in earlier studies, its link with innovation behaviour has remained relatively underexplored. This study aims to fill this gap through investigating whether, and if so, how, top executive turnover event influences firms' R&D investment. Based on a sample of 2, 810 A-share listed companies in China for the period 2008–2016, our results suggest that top executive turnover is negatively related to enterprises' R&D investment. This is mainly because top executive turnover increases the departure rate of R&D personnel, which worsens enterprises' internal R&D environment. The findings also indicate that the negative effect of top executive turnover on R&D investment is accentuated for family enterprises and non-state-owned corporations. Our results have implications for the literature on top executive turnover and enterprises' innovation behaviour and can inform practice, particularly with respect to the selection of top management team members.